Impacts of psychological wellbeing with HIV/AIDS and cancer among sexual and gender minorities: A systematic review and meta-analysis - Alex Siu Wing Chan; Lok Man Leung; Jane Siu Fan Li; Jacqueline Mei Chi Ho; Hon Lon Tam; Wing Leung Hsu; Wing Leung Hsu; April Nicole On Sang Iu; Patrick Ming Kuen Tang; Elsie Yan (Frontiers Media S.A., 2022)
BackgroundThe agony and economic strain of cancer and HIV/AIDS therapies severely impact patients' psychological wellbeing. Meanwhile, sexual minorities experience discrimination and mental illness. LGBT individuals with cancer and HIV/AIDS play two roles. It is important to understand and examine this groups mental wellbeing.ObjectiveThe purpose of this study is to synthesize current studies on the impact of HIV/AIDS and cancer on LGBT patients' psychological wellbeing.MethodsThis research uses a systematic literature review at first and later stage a meta-analysis was run on the same review. In this study, data from Google academic and Web of Science has been used to filter literature. PRISMA 2020 Flow Diagram seeks research on LGBT cancer and HIV/AIDS patients. The above sites yielded 370 related papers, some of which were removed due to age or inaccuracy. Finally, meta-analyses was done on 27 HIV/AIDS and 33 cancer patients's analyse.ResultsThe research included 9,898 LGBT cancer sufferers with AIDS and 14,465 cancer sufferers with HIV/AIDS. Using meta-analysis, we discovered the gap in psychological wellbeing scores between HIV/AIDS LGBT and non-LGBT groups ranged from −10.86 to 15.63. The overall score disparity between the HIV/AIDS LGBT and non-LGBT groups was 1.270 (95% CI = 0.990-1.560, Z = 86.58, P < 0.1). The disparity in psychological wellbeing scores between cancer LGBT group and general group varies from −8.77 to 20.94 in the 34 papers examined in this study. Overall, the psychological wellbeing score disparity between the cancer LGBT subset and the general group was 12.48 (95% CI was 10.05-14.92, Test Z-value was 268.40, P-value was <0.1).ConclusionInflammation and fibrosis in HIV/AIDS and cancer sufferers adversely affect their psychological wellbeing.